2013
DOI: 10.4103/0973-1296.108136
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 10 components in traditional Chinese medicine Dachaihu Granule by reversed-phase-high-performance liquid chromatographic-diode array detector

Abstract: Background:Dachaihu Granule, commonly used for treating cholecystitis, is derived from a famous traditional Chinese formula named Dachaihu Decoction. No analytical method has been reported for simultaneous determination of 10 bioactive compounds for quality control in Dachaihu Granule so far.Objective:To develop a high-performance liquid chromatographic (HPLC) method with diode array detector (DAD) for simultaneous determination of 10 bioactive compounds (paeoniflorin, aloe-emodin, rhein, emodin, chrysophanol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The SFDA suggested that all herbal chromatograms should be evaluated in terms of similarity by calculating the correlation coefficient and/or angle cosine value of the original data. [ 16 17 18 ] Therefore, SA was conducted based on the mean peak area of standard fingerprints using correlation coefficient method and the cosine of the angle method to calculate the similarity of fingerprints. The same samples had similar constituents with the slight difference resulting from the BZZW and RZZW.…”
Section: Resultsmentioning
confidence: 99%
“…The SFDA suggested that all herbal chromatograms should be evaluated in terms of similarity by calculating the correlation coefficient and/or angle cosine value of the original data. [ 16 17 18 ] Therefore, SA was conducted based on the mean peak area of standard fingerprints using correlation coefficient method and the cosine of the angle method to calculate the similarity of fingerprints. The same samples had similar constituents with the slight difference resulting from the BZZW and RZZW.…”
Section: Resultsmentioning
confidence: 99%
“…The herbal formulation abnormal savda munziq (ASMQ) tang of the traditional Uighur medicine from the Xinjiang region of China is used to treat complex diseases such as cancer, diabetes, and cardiovascular diseases. [ 1 2 3 4 5 ] This formulation is composed of 10 medicinal herbs, namely, Cordia dichotoma Forst. f, Anchusa italica Retz., Euphorbia humifusa Willd., Adiantum capillus-veneris L., Ziziphus jujube Mill., Glycyrrhiza uralensis , Foeniculum vulgare Mill., Lavandula angustifolia Mill., Dracocephalum moldavica L., and Alhagi pseudoalhagi Desv.…”
Section: Introductionmentioning
confidence: 99%
“…Shaoyao-Gancao decoction (SGD) is a popular traditional Chinese medicine (TCM) and Shakuyaku-Kanzo-to in Japanese, firstly recorded in Shang Han Lun in Han Dynasty of Chinese history (202 BC-220 AD). [ 1 ] Its recipe is composed of two herbal medicines, Paeoniae Radix and Glycyrrhizae Radix , mainly used for the treatment of abdominal pain and dysmenorrhea disease. [ 2 ] Modern pharmacological studies have demonstrated that SGD carries various attractive biological activities.…”
Section: Introductionmentioning
confidence: 99%